Factors Influencing User Adoption of Artificial Intelligence in the Telecommunications Industry: Challenges and Strategic Approaches - Mumpanshya , Elitas; Mbale, Jameson (Proceedings of International Conference for ICT (ICICT) - Zambia, 2025)
The potential of Artificial Intelligence (AI) to revolutionize the telecommunications sector is undeniable, offering opportunities to enhance service delivery, boost operational efficiency and elevate customer experiences. Despite its growing prominence across industries, the widespread adoption of AI within telecommunications remains a multifaceted challenge. This paper investigates the critical factors influencing users' adoption of AI technologies in this sector, with a particular focus on technological readiness, perceived benefits, ethical considerations, data privacy concerns and socioeconomic barriers. The study highlights how telecommunications companies must address these diverse elements to effectively promote AI adoption among users. Specific strategies discussed include enhancing user awareness of AI's advantages, implementing robust data security protocols and ensuring transparency in AI systems. Furthermore, the paper emphasizes the need for tailored AI solutions that cater to a broad spectrum of user demographics, especially those from lower socioeconomic backgrounds, to foster more inclusive adoption. By providing a comprehensive analysis of these factors, the paper contributes to the existing literature on AI adoption in telecommunications and offers actionable recommendations for industry stakeholders. The findings aim to inform decision-makers in the telecommunications industry on how to overcome adoption barriers, drive innovation and enhance the overall service experience through AI integration.